2009
DOI: 10.1111/j.1365-2303.2008.00594.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic pitfalls in the evaluation of fine needle aspiration cytology of the thyroid: correlation with histopathology in 260 cases

Abstract: Diagnostic pitfalls in the evaluation of fine needle aspiration cytology of the thyroid: correlation with histopathology in 260 cases Objectives: Fine needle aspiration cytology (FNAC) of the thyroid is a non-invasive, cost-effective screening procedure that is valuable for distinguishing neoplastic lesions from non-neoplastic nodules. The aim of this study was to determine the diagnostic accuracy of FNACs performed at our institution by correlating FNAC results with histopathological diagnoses. Methods: Two h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
56
3
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 16 publications
(40 reference statements)
12
56
3
4
Order By: Relevance
“…The false negative rate of 31 % was much higher than the target of 0-5% and the false positive rate was higher than recommended at 23%. Compared to a similar study in 2008 [6] which found a sensitivity of 92.6%, a specificity of 91.6% and a false negative rate of 2.3%, our local department rates need significant improvement, particularly for sensitivity and false positive/negative rates. A specificity of 80% suggests that local pathologists are good at identifying true negative cases.…”
Section: Correlation With Histology and Ppvcontrasting
confidence: 71%
“…The false negative rate of 31 % was much higher than the target of 0-5% and the false positive rate was higher than recommended at 23%. Compared to a similar study in 2008 [6] which found a sensitivity of 92.6%, a specificity of 91.6% and a false negative rate of 2.3%, our local department rates need significant improvement, particularly for sensitivity and false positive/negative rates. A specificity of 80% suggests that local pathologists are good at identifying true negative cases.…”
Section: Correlation With Histology and Ppvcontrasting
confidence: 71%
“…Most studies presented the incidence of HT in surgically resected PTC cases. In cytology specimens of HT patients, follicular cells often exhibit nuclear elongation, nuclear grooves, and even intranuclear inclusions, leading to a misdiagnosis of PTC (45,46). Therefore, the current meta-analysis included only the studies that presented cases of HT confirmed by histopathologic diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…19 . HT varlığında, nükleer genişle-me, agregasyon, intranükleer inklüzyon ve atipik bulguların (fibrozis, lenfositik infiltrasyon, hurthle hücre metaplazisi) varlığı TPK ile karıştırılmaya yol açabilir ve yanlış tanıya sebep olabilir 20,21 .…”
Section: Materyal Ve Metotunclassified
“…Diğer bir çalışmada duyarlılık %92,6, özgüllük %91,6, tanısal uygunluk %91,9, pozitif öngörü değeri 83,3 ve negatif öngörü değeri %96,5 bulunmuştur 21 . Burch ve ark.…”
Section: Materyal Ve Metotunclassified